Pancreatic Cancer and Diabetes: A Scientific Analysis - Kumari Shachi; Sanjeev Kumar (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Pancreatic cancer is most often detected at an advanced stage due to a lack of symptoms at the first stage. Pancreatic cancer is relatively uncommon, and screening of the asymptomatic population is not feasible or cost-effective. Therefore, screening of individuals in high-risk groups is recommended. Diabetes mellitus (DM) is associated with pancreatic cancer, and patients with DM are recognized as a high-risk group for pancreatic cancer. This review article shows a scientific analysis between pancreatic cancer and diabetes, including the role of diabetes as a risk factor for pancreatic cancer and its role in inducing the destruction of islet \(β\) cells and insulin resistance. Pancreatic cancer causes diabetes and diabetes is a risk factor for the development of pancreatic cancer.